Rural development in West Bengal - Mandal Amal (New Delhi Northern Book Centre, 2005)
This book presents a comprehensive account of few rural development issues like panchayat politics, panchayat finance, panchayat leadership, people;s participation, primary education, public health and tea garden.
Keywords: India; Panchayats; Rural development; West Bengal